2012
DOI: 10.1016/j.bbrc.2012.02.118
|View full text |Cite
|
Sign up to set email alerts
|

A pro-inflammatory role of deubiquitinating enzyme cylindromatosis (CYLD) in vascular smooth muscle cells

Abstract: CYLD, a deubiquitinating enzyme (DUB), is a critical regulator of diverse cellular processes, ranging from proliferation and differentiation to inflammatory responses, via regulating multiple key signaling cascades such as nuclear factor kappa B (NF-κB) pathway. CYLD has been shown to inhibit vascular lesion formation presumably through suppressing NF-κB activity in vascular cells. However, herein we report a novel role of CYLD in mediating pro-inflammatory responses in vascular smooth muscle cells (VSMCs) via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Apparently, knockout of CYLD did not affect albumin or peroxide-related cell death in human epithelial HK-2 cells, but it did increase ICAM-1 and JNK levels upon TNFα stimulation. Another report dealt with the vascular smooth muscle cells (VSMCs) in the aortic arch, thought to be involved in lesion formation [13]. An adenoviral knockdown of CYLD showed a notable decrease in TNFα-induced inflammatory cytokines Mcp-1, IL-6 and ICAM-1.…”
Section: Cyld and The Cardiovascular System: A New Frontiermentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, knockout of CYLD did not affect albumin or peroxide-related cell death in human epithelial HK-2 cells, but it did increase ICAM-1 and JNK levels upon TNFα stimulation. Another report dealt with the vascular smooth muscle cells (VSMCs) in the aortic arch, thought to be involved in lesion formation [13]. An adenoviral knockdown of CYLD showed a notable decrease in TNFα-induced inflammatory cytokines Mcp-1, IL-6 and ICAM-1.…”
Section: Cyld and The Cardiovascular System: A New Frontiermentioning
confidence: 99%
“…Exploration then continued with the thought of CYLD as being a tumor suppressor and inflammatory control factor, especially in the skin [9, 10]. As more pathogen responses and developmental aspects of cellular biology began to be linked to inflammation, CYLD’s role as a master regulator of NF-kB-induced inflammation came into the forefront as a factor that could switch off NF-kB and prevent tissue damage that leads to necrosis, cancer and loss of cell proliferation [1113]. From 2009, many reports detailing specific instances in diverse tissue types (such as lungs, immune cells, breast tissue and bone) where CYLD loss of function is deleterious have been published [1422].…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte infiltration is guided by chemotactic factors, and the release of cytokines recruits additional inflammatory cells. Adhesion molecules such as ICAM-1 and chemokines such as MCP-1 are fundamental to inflammatory processes [32]. Inoue et al [33] demonstrated that serum levels of ICAM-1 significantly increased in human coronary sinus blood samples immediately after angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…CYLD is a DUB controlling inflammatory responses via regulating such signalling cascades as nuclear factor kappa B (NF-κB) pathway [1214]. Specifically, it has been shown to down-regulate NF-κB activation through deubiquitination of TRAF2, 6, and 7, therefore preventing the formation of an antiviral response [1417].…”
Section: The Host Immune Responses Regulated By Dubsmentioning
confidence: 99%
“…Specifically, it has been shown to down-regulate NF-κB activation through deubiquitination of TRAF2, 6, and 7, therefore preventing the formation of an antiviral response [1417]. E3 ligase Itch and deubiquitinase CYLD form a complex that cleaves lysine (Lys) 63-linked ubiquitin chains and catalyze Lys48-linked ubiquitination on the kinase Tak1, which is a common substrate for these two proteins, thereby contributing to decreased inflammatory signalling [18].…”
Section: The Host Immune Responses Regulated By Dubsmentioning
confidence: 99%